2005
DOI: 10.1677/erc.1.00920
|View full text |Cite
|
Sign up to set email alerts
|

Identification of growth factor independent-1 (GFI1) as a repressor of 25-hydroxyvitamin D 1-alpha hydroxylase (CYP27B1) gene expression in human prostate cancer cells

Abstract: The hormone 1,25-dihydroxyvitamin D (1,25D) may play a protective role in prostate cancer. 25-hydroxyvitamin D 1-a hydroxylase (CYP27B1) is the enzyme responsible for the regulation of cellular 1,25D levels. CYP27B1 is substantially repressed in prostate cancer cells. We have investigated the molecular basis for this inhibition. First, we identify a repressive region between -997 and -1200 in the human CYP27B1 promoter following transient transfection analysis in the prostate cancer cell lines DU145, PC3 and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…CBFA2T1 and CBFA2T3 have previously been shown to interact with GFI-1, a zinc-finger transcription repressor (14). We recently showed that GFI-1 represses 25-hydroxyvitamin D 1a-hydroxylase (CYP27B1) expression in human prostate cancer cells, and that this repression is mediated through GFI-1 -specific, DNA-binding sequences within the CYP27B1 promoter (28). Reporter assays were done to investigate if the ETO proteins differ in their ability to further repress the GFI-1 -mediated transcriptional repression from the CYP27B1 promoter.…”
Section: Gfi-1 Transcriptional Repression Is Specifically Enhanced Bymentioning
confidence: 99%
See 1 more Smart Citation
“…CBFA2T1 and CBFA2T3 have previously been shown to interact with GFI-1, a zinc-finger transcription repressor (14). We recently showed that GFI-1 represses 25-hydroxyvitamin D 1a-hydroxylase (CYP27B1) expression in human prostate cancer cells, and that this repression is mediated through GFI-1 -specific, DNA-binding sequences within the CYP27B1 promoter (28). Reporter assays were done to investigate if the ETO proteins differ in their ability to further repress the GFI-1 -mediated transcriptional repression from the CYP27B1 promoter.…”
Section: Gfi-1 Transcriptional Repression Is Specifically Enhanced Bymentioning
confidence: 99%
“…To generate pGL2-GAL4-TK-luciferase construct, 5 ¶ and 3 ¶ ends of the XbaIBamHI fragment carrying 5Â GAL4 DNA-binding sequences from pG5CAT (Promega, Madison, WI) were filled-in using Klenow DNA polymerase and cloned at blunted XhoI site of pGL2-TK-luciferase. Constructs used for GFI-1 -mediated repression assays were pCYP27B1WT(À1200)-Luc that contained a 1,244 bp region of the CYP27B1 promoter (À1200 together with 44 bp of CYP27B1 5 ¶ untranslated region), pCYP27B1Enh(À997)-Luc that was deleted for the region containing the GFI-1 consensus binding site, and pCYP27B1mGFI (-1200)-Luc that contained mutated GFI-1 binding site (28). The construct expressing FLAG-GFI-1 was kindly provided by H.L.…”
Section: Plasmidsmentioning
confidence: 99%
“…Gfi-1 has further been shown to cooperate with c-Myc and Pim1 in lymphomagenesis. In addition, Gfi-1 may play a role in lung and prostate cancers (3,4).…”
mentioning
confidence: 99%
“…Gfi-1 and its paralog Gfi-1b are also involved in hematopoiesis (Zeng et al 2004;Duan and Horwitz 2005) and immune system function (Schmidt et al 1998b;Karsunky et al 2002;Zhu et al 2002;Hock et al 2003;Yucel et al 2003;Zeng et al 2004;Rathinam et al 2005) and have been implicated in disease processes including neutropenia (Karsunky et al 2002;Person et al 2003), carcinogenesis (Gilks et al 1993;Schmidt et al 1996Schmidt et al , 1998aHock et al 2004;Kazanjian et al 2004;Shin et al 2004;Dwivedi et al 2005), and neurodegenerative disease (Moroy 2005;Tsuda et al 2005). The expression of both sens and Gfi-1 is positively regulated by the bHLH proneural gene atonal/Math-5.…”
mentioning
confidence: 99%